AN INDIRECT ROTOR-FLUX-ORIENTED CONTROL OF A TWO-PHASE INDUCTION MOTOR DRIVE (Journal of Engineering, 2008)
A vector control is proposed for a two phase induction motor drive . The motor is driven by H-bridge current-regulated pulsewidth modulated voltage source inverter. The vector control is based upon rotor field orientation concepts that have been adopted for this type of machine. Simulation results are provided to illustrate the system operation and the MATLAB/SIMULINK has been used for simulation.